2003
DOI: 10.1177/8756479303252896
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Evaluation of Fibromatosis (Aggressive Type) Using Color Doppler Interrogation

Abstract: Fibromatosis refers to formation of a fibrous or tumor-like nodule or nodular swelling arising from fascia or connective tissue. The behavior of fibromatosis ranges from a self-limiting benign condition to the aggressive or recurrent type. No articles at this time have reported cases of aggressive fibromatosis emphasizing the use of color Doppler sonography for preoperative planning. The authors report two cases of aggressive fibromatosis interrogated with color Doppler imaging and magnetic resonance imaging t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Generally, extra-abdominal desmoid tumors occur in deeper limb tissue and have no obvious contact with the tendon sheath or joint capsule. [31][32][33] As with all retrospective studies, this one had limitations. First, a selection bias was a possible confounding factor because all the cases in this study were identified by histopathologic examination.…”
Section: D a Bmentioning
confidence: 99%
“…Generally, extra-abdominal desmoid tumors occur in deeper limb tissue and have no obvious contact with the tendon sheath or joint capsule. [31][32][33] As with all retrospective studies, this one had limitations. First, a selection bias was a possible confounding factor because all the cases in this study were identified by histopathologic examination.…”
Section: D a Bmentioning
confidence: 99%
“…Occasionally marked vascularity may be seen in cases of aggressive fibromatosis. 6 The CT and magnetic resonance imaging are useful imaging techniques, which help in the evaluation of the size, site, and extent of the lesion, as well as for monitoring therapeutic response and assessment of complications. 3,4 On CT scan, desmoids may appear homogeneous or heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…Few reports have emphasized the blood flow distribution of desmoid tumors 18 , 19 . In a report by Taggart and Kavic, 19 marked vascularity shown on color Doppler imaging in 2 cases was associated with the more aggressive type of fibromatosis and documented by surgery. In our series, 14 lesions (58.3%) had substantial flow (Figures 2B and 3B), 8 (33.3%) had minimal flow, and 2 (8.3%) that were smaller than 2.0 cm had no flow.…”
Section: Discussionmentioning
confidence: 99%